Engineering mesenchymal stem cells to improve their exosome efficacy and yield for cell-free therapy. Issue 1 (1st December 2018) - Phan, Jennifer; Kumar, Priyadarsini; Hao, Dake; Gao, Kewa; Farmer, Diana; Wang, Aijun
ABSTRACT: Through traditional medicine, there were diseases and disorders that previously remained untreated or were simply thought to be incurable. Since the discovery of mesenchymal stem cells (MSCs), there has been a flurry of research to develop MSC-based therapy for diseases and disorders. It is now well-known that MSCs do not typically engraft after transplantation and exhibit their therapeutic effect via a paracrine mechanism. In addition to secretory proteins, MSCs also produce extracellular vesicles (EVs), membrane-bound nanovesicles containing proteins, DNA and RNA. The secreted vesicles then interact with target cells and deliver their contents, imparting their ultimate therapeutic effect. Unlike the widely studied cancer cells, the yield of MSC-exosomes is a limiting factor for large-scale production for cell-free therapies. Here we summarise potential approaches to increase the yield of such vesicles while maintaining or enhancing their efficacy by engineering the extracellular environment and intracellular components of MSCs.